The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5935/0101-2800.20150032
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in serum albumin: impact on 2-year mortality in incident hemodialysis patients

Abstract: Early sAlb changes showed a significant predictive power on mortality at 2 years in incident hemodialysis patients. Those with low initial sAlb may have a better prognosis if their sAlb rises. In contrast, patients with satisfactory initial levels can have a worsening of their prognosis in the case of an early reduction in sAlb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The poorer control of hypertension in AAs (who are genetically related to our study population) coupled with poor compliance with the use of BP lowering drugs, is expected to produce lower dialysis doses, higher extraction ratio, IDWG and ultrafiltration volume [29]. The inverse relationship between the UFV and the predialysis values of serum albumin, bicarbonate and haematocrit in our study mirror findings from studies that reported that the extraction ration, IDWG and UFV increases with derangement in serum biochemical parameters [29][30][31]. Prolonged dialysis session allow for reductions in UFR in those prone to IDH, the lower dose from this is compensated for by increased dose from dialysis prolongation hence preventing IDH is worth it [25].…”
Section: Discussionsupporting
confidence: 78%
“…The poorer control of hypertension in AAs (who are genetically related to our study population) coupled with poor compliance with the use of BP lowering drugs, is expected to produce lower dialysis doses, higher extraction ratio, IDWG and ultrafiltration volume [29]. The inverse relationship between the UFV and the predialysis values of serum albumin, bicarbonate and haematocrit in our study mirror findings from studies that reported that the extraction ration, IDWG and UFV increases with derangement in serum biochemical parameters [29][30][31]. Prolonged dialysis session allow for reductions in UFR in those prone to IDH, the lower dose from this is compensated for by increased dose from dialysis prolongation hence preventing IDH is worth it [25].…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, our study indicates that total circulating albumin as well as essential electrolytes in plasma, except K + , are substantially decreased following HD. The current observation that circulating albumin, a strong mortality risk factor in ESRD patients, [2][3][4][5] is reduced by HD in proportion to PV withdrawal merits particular attention. According to regression analyses, for every liter of plasma removed by HD, approximately 40 g of albumin, i.e., one third of total circulating albumin, are lost from the intravascular compartment.…”
Section: Discussionmentioning
confidence: 98%
“…In patients with end‐stage renal disease (ESRD), abnormally low plasma albumin limits fluid shifts from edematous tissues into the circulation, where excess fluid can be removed via the hemodialysis (HD) procedure. Importantly, hypoalbuminemia (hALB) is a strong prognostic factor of death and cardiovascular complications in ESRD patients 2–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KDOQI guidelines recommend timely nephrology referral, nutritional consultation, fistula placement for dialysis access, control of anemia, acidosis, and mineral and bone metabolism parameters [5]. Several studies suggest that there is a significant correlation between the number of KDOQI guidelines with survival and quality of life [6][7][8], at least in the first year after the initiation of renal replacement therapy [9]. However, only 1.6% of patients with ESRD on hemodialysis achieve 3 goals [1,10].…”
Section: Introductionmentioning
confidence: 99%